2012
DOI: 10.1590/s0102-695x2011005000214
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from the fungus Scleroderma nitidum with anti-inflammatory potential modulate cytokine levels and the expression of Nuclear Factor kB

Abstract: Several pharmacological properties are attributed to polysaccharides and glucans derived from fungi such as tumor, anti-inflammatory, and immunomodulatory activity. In this work, the anti-inflammatory potential of polysaccharides from the fungus Scleroderma nitidum and their possible action mechanism were studied. The effect of these polymers on the inflammatory process was tested using the carrageenan and histamine-induced paw edema model and the sodium thioglycolate and zymosan-induced model. The polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Aqueous extracts from mushrooms have long been used in oriental medicine as natural drugs. In addition, several studies have demonstrated the pharmacological potential of these extracts [ 45 47 ]. Fungal polysaccharides have severe effects on a variety of leukocytes, including macrophages, neutrophils, eosinophils and NK cells, as well as non-immune cells, such as endothelial cells, alveolar epithelial cells and fibroblasts [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extracts from mushrooms have long been used in oriental medicine as natural drugs. In addition, several studies have demonstrated the pharmacological potential of these extracts [ 45 47 ]. Fungal polysaccharides have severe effects on a variety of leukocytes, including macrophages, neutrophils, eosinophils and NK cells, as well as non-immune cells, such as endothelial cells, alveolar epithelial cells and fibroblasts [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%